The Relationship Between Uric Acid Levels and Random Blood Glucose in the Elderly in Mas Village, Ubud Subdistrict, Gianyar Regency - Ni Putu Kireina Karnita; I Gusti Agung Dewi Sarihati; Ida Ayu Made Sri Arjani (Borneo Scientific Publishing, 2024)
Elderly individuals are those who have reached the age of 60 years and above. Older adults have a potential risk of increased uric acid and blood glucose levels due to the decline in organ function caused by aging cells. This study aims to determine the relationship between uric acid levels and random blood glucose in the elderly in Mas Village, Ubud Subdistrict, Gianyar Regency. This research is an analytical observational study with a cross-sectional design, involving independent and dependent variables collected simultaneously. The sample size consists of 32 respondents selected through purposive sampling based on inclusion and exclusion criteria. Uric acid and random blood glucose levels were measured using an Easy Touch device. The research results were analyzed using the chi-square correlation test, yielding a p-value of 0.454, which is greater than α (0.05). It can be concluded that there is no significant relationship between uric acid levels and random blood glucose levels in the elderly.